Giant hemangiomas of the skeletal muscle - Minasián, Pablo; Barberousse, Carlos; Sánchez, Gustavo; Bazzino, Luis (Cirugía del Uruguay, 2006)
We report two cases of skeletal muse/e haemangioma, one of them of the trapezoid muse/e and the other paravertebral muse/es. They were teated by a block rection of the tumour and the muse/ e among them. They were treated by a block resection of the tumour and the muse/e among them. The outcome was favourab/e without seque/ae. A complete review was done and dagnostic, treatment and outcome aspects were established. We conclude that the possibiity of a muse/e haemangioma must be suspected in evey case and the best study is the RMN. The standard treatment is block resection without radica/ity because the benign nature of the tumour.